Cover Image, Volume 14, Issue 2. (June 2016) - Finotello, R.; Ressel, L.; Arvigo, M.; Baroni, G.; Marchetti, V.; Romanelli, G.; Burrow, R.; Mignacca, D.; Blackwood, L.
Abstract : The cover image, by Riccardo Finotello et al., is based on the Original Article Canine pancreatic islet cell tumours secreting insulin‐like growth factor type 2 (IGF‐II): a rare entity, DOI:10.1111/vco.12085 . Abstract : The cover image, by Riccardo Finotello et al., is based on the Original Article Canine pancreatic islet cell tumours secreting insulin‐like growth factor type 2 (IGF‐II): a rare entity, DOI:10.1111/vco.12085 .